Midiatização e identidade transfronteiriça: análise de relações dialógicas das canções de Chito de Mello - Dewes, Helyna (2022)
This thesis proposes that the updating of the cross-border identity, which expresses the work of the musician Chito de Mello, is predominantly modulated by the platina sonority in portuñol to establish an inquiry of axiological values of nationality. The new possibilities for social interaction, the ones brought to action and/or virtualized by mediatization, project discursive interactions that soak their musical language from its historic time and social space. These impressions come from a deep ongoing mediatization, reinforcing the relation among media, culture and language as an important asset in the constitution of cultural identities. These technological transformations result in social interactions mediated by devices and platforms, organized by the look of logic in different levels, being included the senses from products of the media way. Songs, composed of both music and lyrics were taken as a communication phenomenon, one that materializes oralty, conveying to the observation of senses that manifest themselves in real communication situations. In this investigation, a analysis of dialogic relationships of the lyrics composing Chito de Mello songs, based on Bakhtin Circle theories is proposed. There is a change from a wider plan to a narrower one, observing the ambiences, surroundings and conditions to get to concrete enunciations, which senses address their identity constitution. It is understood that the identities updating occur through the enunciation and, as a consequence, through interaction, and that is where categories that drive this analysis can be articulated: chronotropy, exotopy and carnavalização. The empiric analysis is retained in the composer, poet and musician’s work, who highlighted Brazil-Uruguay border in his songs. Here, there is the voice of the border, cofounded by the portunhol as language and identity mark and, also, the ways of living that are present in the space between two national States; constituted by cross-borders subjects. Therefore, axiological statements by Chito de Mello’s discursive subject can be observed, once the mediatization process conveys interaction, bringing meaning to his work, from poetic-musical utterances that remain in circulation and can be updated whenever they meet other subjects.